Constructing Alternative Socio-technical Worlds: Re-imagining RRI through SRI in India. (July 2020) - Prasad, C Shambu
While Responsible Research and Innovation has the potential for democratising the governance of research and innovation, translating it in the Global South would need dialogues and engaging with the plural knowledge systems and ongoing experiments on innovation at the margins that seek to construct alternatives. Entrenched power relations in the South do not allow for public dialogues that allows for society to engage with, if not speak back, to scientists in co-creating newer knowledge. Through the case study of the System of Rice Intensification (SRI), an agroecological innovation that arose outside the formal research establishment, we show how vulnerable farming communities can proactively co-create alternatives to existing dilemmas in Indian agriculture. Re-imaging RRI in India, we suggest, requires closer attention to the role of civil society organisations in creating innovation spaces through informal and heterogeneous networks of social learning. Networks, we suggest, allow for better expression of creative dissent that could open newer vistas and alternative framing of knowledge. The RRI agenda is thus incomplete without an engagement with the politics of knowledge, and scientific controversies reveal technological lock-ins that hinders alternative framings and pathways.